A SYSTEMATIC REVIEW ON THE ROLE OF ARTOCARPUS HETEROPHYLLUS (JACKFRUIT) IN CANCER RESEARCH - Abdul Razak, Nurul Syamilah; Ngah Sayuddin , Engku Nasiha Engku; Rostam, Muhamad Ashraf (International Journal of Allied Health Sciences, 2022)
Introduction: Artocarpus heterophyllus, otherwise known as jackfruit, has been proven to possess several pharmacological properties. However, many remain unaware of its potential to exhibit chemopreventive effects against the development and growth of various types of cancer. Therefore, this study aimed to review present literature on the role of Artocarpus heterophyllus and its derivatives in preventing and suppressing cancer growth. Methods: Studies were identified through seven electronic databases based on six keywords and were included if they met the following criteria: described the interventions towards in vitro samples, specifically human cancer cells, compared the growth of cancer cells between treated and untreated control groups, were peer reviewed articles, and published in English in the year 2010 onwards. Results: In total, 755 relevant abstracts were screened, and 32 full-text articles were evaluated. The final ten included studies showed positive results whereby Artocarpus heterophyllus demonstrated significant cytotoxic activity, acting in a dose dependent manner. The most valuable part of the plant exhibiting the strongest anticancer properties was the seeds, in which jacalin, artocarpin and artinM were the major compounds associated with anticancer activity. Breast, lung, and colon cancer cells were most commonly used to investigate the chemopreventive properties of Artocarpus heterophyllus. Conclusion: This review compiles evidence of the potential chemopreventive properties of Artocarpus heterophyllus and the outcome of this review is expected to be beneficial in promoting the utilization of Artocarpus heterophyllus in alternative treatments for cancer.